Harnack inequality under the change of metric. (March 2015) - Tasena, Santi; Saloff-Coste, Laurent; Dhompongsa, Sompong
Abstract: In this work, we give a sufficient and necessary condition in which the (parabolic) Harnack inequality of the original space would imply that of quasi-conformal spaces. The result can be applied to a large class of functions with discrete singularities.